Penerapan Metode Weighted Product dalam Sistem Pendukung Keputusan Program Penerimaan Bantuan Beras - Iqbal Ramadhani Mukhlis; Thomas Aquino Berno Doduk; Tri Puspa Rinjeni; Virdha Rahma Aulia; Rafika Rahmawati; Tri Luhur Indayanti Sugata; Prasasti Karunia Farista Ananto; Nambi Sembilu (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2024)
This study aims to develop an effective Decision Support System (DSS) in the process of the rice aid program. The Weighted Product (WP) method is used as the basis for decision-making to determine the receipt of rice aid. This DSS is designed to assist program organizers in selecting rice aid recipients more efficiently and objectively. The Weighted Product method is used to calculate the weight value of each criterion given by the rice aid recipient. This study's results can positively contribute to increasing efficiency and transparency in decision-making for the rice aid program. With this Weighted Product-based DSS, it is hoped that the selection process for rice aid recipients can be carried out more objectively and measurably so that the program's benefits can be more evenly distributed and targeted.